Cultural Heritage Concept, Genealogy and Contemporary Challenges - Forero, Juliana; Hong, Liangping (Richtmann Publishing, 2012)
This document aims to analyze the genealogy of the concept of cultural heritage from the Middle Ages tothe twenty-first century, to establish the reason why it is still necessary to review and reconceptualize theway to understand the cultural heritage, where the material and immaterial aspects mutually interactaccording to its socio-cultural functions. The impacts of the market economy over the cultural heritagedefinition and management after the second part of the twentieth century make evident why culturalheritage preservation has to be redirected and redefined. It has to involve not only the communities’perspective and interests, but also different cultural heritage dynamics and understandings out theEurocentric perspective that still rules heritage issues.